Sistem Informasi Kinerja Sekolah Dan Guru Di Dinas Pendidikan Kabupaten Gorontalo Berbasis Web - Fadik Sadjar; Sitti Suhada; Edi Setiawan (Diffusion: Journal of Systems and Information Technology, 2021)
Teacher performance assessment is the assessment of each item of activities of teacher's main tasks for the purposes of career, rank, and position development. School accreditation is a systematic and comprehensive assessment for school through self-evaluation and external evaluation (visitation) in order to determine the feasibility and performance of the school. The observation results revealed that the school and teacher performance assessment records were still in the form of archive documents, which were less effective and accurate. Meanwhile, the data storage also used manual system. Therefore, based on the aforementioned problem, this research aimed to design an information system at the Education Board of Gorontalo Regency. System development employed waterfall method, a classical method with systematic and sequential model in terms of software development. The method consisted of five stages, namely : 1) analysis, 2) system design, 3) system implementation, 4) system testing, 5) system maintenance, and also used PHP programming language and MySQL database. The results showed that this application was dependable in assisting the school and the accessor in terms of assessing the performance of teacher and school, respectively.